2021
DOI: 10.1021/acsnano.1c02719
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Graphene Oxide Membranes with pH-Responsive Nanochannels for High-Performance Nanofiltration

Abstract: Tunable gating graphene oxide (GO) membranes with high water permeance and precise molecular separation remain highly desired in smart nanofiltration devices. Herein, bioinspired by the filtration function of the renal glomerulus, we report a smart and high-performance graphene oxide membrane constructed via introducing positively charged polyethylenimine-grafted GO (GO-PEI) to negatively charged GO nanosheets. It was found that the additional GO-PEI component changed the surface charge, improved the hydrophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(70 citation statements)
references
References 50 publications
(77 reference statements)
1
68
0
Order By: Relevance
“…The above results reasonably illustrate the charge-dominated separation of charged molecules. [38] In addition, the TpEB membrane preserves high rejections to molecules with molecular weights >900 Da in ethanol, indicating the contribution of size-based exclusion to separation performances. Therefore, based on the above discussion, we conclude that the excellent nanofiltration performance of TpEB membranes is synergistically dominated by sizes and charges.…”
Section: Molecular Separation Performances Of Tpeb Membranesmentioning
confidence: 97%
“…The above results reasonably illustrate the charge-dominated separation of charged molecules. [38] In addition, the TpEB membrane preserves high rejections to molecules with molecular weights >900 Da in ethanol, indicating the contribution of size-based exclusion to separation performances. Therefore, based on the above discussion, we conclude that the excellent nanofiltration performance of TpEB membranes is synergistically dominated by sizes and charges.…”
Section: Molecular Separation Performances Of Tpeb Membranesmentioning
confidence: 97%
“…e Schematic diagram of EG modified GO [78]. f Schematic illustration of pH-responsive nanochannels [79] allows water to pass through quickly and its permeability is negatively correlated with the thickness of the membrane, the water permeation schematic is shown in the Fig. 3c.…”
Section: Water Treatmentmentioning
confidence: 99%
“…Due to the good water permeability and high rejection of macromolecules, GO/EG membranes can be used for water purification. Zhijie Zhang et al [79] prepared a smart and high-performance GO membrane inspired by the biology of glomerular filtration function, which was constructed by introducing positively charged polyethyleneimine grafted GO (GO-PEI) into negatively charged GO nanosheets. It was found that the additional GO-PEI component changed the surface charge, improved hydrophilicity, and enlarged the nanochannels.…”
Section: Water Treatmentmentioning
confidence: 99%
“…Tunable mass transport is of fundamental importance not only in separation-based applications but also in biological sensing, drug delivery, , catalysis, , nanofluidics, , proton transport, and energy harvesting . Responsive nanochannels with tunable sieving diameters are the best candidates for such applications. To date, stimuli, such as heat, environmental pH, , ions/molecules, , and light, have been used to produce controllable responses of nanochannels, but challenges remain, particularly in terms of stimulus complexity (e.g., solutions and ions) and response uncontrollability (e.g., low durability and response rate) …”
Section: Introductionmentioning
confidence: 99%
“…34 Responsive nanochannels with tunable sieving diameters are the best candidates for such applications. 35−37 To date, stimuli, such as heat, 38 environmental pH, 39,40 ions/molecules, 41,42 have been used to produce controllable responses of nanochannels, but challenges remain, particularly in terms of stimulus complexity (e.g., solutions and ions) and response uncontrollability (e.g., low durability and response rate). 36 Herein, we computationally investigate the actuation performance of Sc 2 C MNTs in response to charge injection.…”
Section: ■ Introductionmentioning
confidence: 99%